1987
DOI: 10.1007/bf00292496
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the variations of ejection fraction during exercise in chronic aortic regurgitation

Abstract: The influence of left ventricular volume variations and regurgitant fraction variations upon left ventricular ejection fraction during exercise was examined using equilibrium radionuclide angiography in patients suffering from aortic regurgitation. Ejection fraction (EF), regurgitant fraction (RF), end diastolic volume (EDV) and end systolic volume (ESV) variations from rest to peak exercise were determined in 44 patients suffering from chronic aortic regurgitation (AR) and in 8 healthy volunteers (C). In C, E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…Furthermore, these variables had predictive value for the risk of sudden cardiac death in the natural history of the disease (3). In the present study, pre-operative EF rest was found to be significantly correlated to EF max , separately both pre-and postoperatively, which was in concordance with previous studies (7,11,25,26). However, pre-operative EF rest was not connected to post-operative EF increase upon exercise and was, therefore, not found to be informative for LV performance during exercise post-operatively.…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, these variables had predictive value for the risk of sudden cardiac death in the natural history of the disease (3). In the present study, pre-operative EF rest was found to be significantly correlated to EF max , separately both pre-and postoperatively, which was in concordance with previous studies (7,11,25,26). However, pre-operative EF rest was not connected to post-operative EF increase upon exercise and was, therefore, not found to be informative for LV performance during exercise post-operatively.…”
Section: Discussionsupporting
confidence: 82%
“…Optimal timing of surgery in chronic aortic regurgitation (AR) remains a challenge. (Bassand et al. , 1987; Bonow, 1994, 2000; Borer et al.…”
Section: Introductionmentioning
confidence: 99%